2016
DOI: 10.1016/j.celrep.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Errors of Long-Chain Fatty Acid β-Oxidation Link Neural Stem Cell Self-Renewal to Autism

Abstract: SUMMARY Inborn errors of metabolism (IEMs) occur with high incidence in human populations. Especially prevalent among these are inborn deficiencies in fatty acid β-oxidation (FAO) clinically associated with developmental neuropsychiatric disorders, including autism. We now report that neural stem cell (NSC)-autonomous insufficiencies in activity of TMLHE (an autism-risk factor that supports long-chain FAO by catalyzing carnitine biosynthesis), of CPT1A (enzyme required for long-chain FAO transport into mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 35 publications
(49 reference statements)
6
103
0
3
Order By: Relevance
“…Along similar lines, inhibition of FA mobilization from lipid droplets or transport into mitochondria reduces the NSC pool in mouse embryonic neocortex by favoring NSC symmetric differentiating division. This observation, which confirms previous findings on the key role of FA oxidation (FAO) in HSC self-renewal [36], is particularly relevant, since inborn defects in FAO are associated with developmental neuropsychiatric disorders including autism in humans [37]. Of note, FAO capacity is not restricted to embryonic NSCs, but also occurs in adult cells from SVZ [38].…”
Section: An Emerging Determinant In Nsc Fate Decisions: Lipid Metabolismsupporting
confidence: 85%
See 1 more Smart Citation
“…Along similar lines, inhibition of FA mobilization from lipid droplets or transport into mitochondria reduces the NSC pool in mouse embryonic neocortex by favoring NSC symmetric differentiating division. This observation, which confirms previous findings on the key role of FA oxidation (FAO) in HSC self-renewal [36], is particularly relevant, since inborn defects in FAO are associated with developmental neuropsychiatric disorders including autism in humans [37]. Of note, FAO capacity is not restricted to embryonic NSCs, but also occurs in adult cells from SVZ [38].…”
Section: An Emerging Determinant In Nsc Fate Decisions: Lipid Metabolismsupporting
confidence: 85%
“…These studies have indeed confirmed that NSC exit from quiescence is marked by downregulation of glycolysis [37], and FAO [38], and by an increase in ribosome biogenesis, protein synthesis, and mitochondrial oxidative phosphorylation.…”
Section: An Emerging Determinant In Nsc Fate Decisions: Lipid Metabolismmentioning
confidence: 50%
“…It is widely supposed that brain did not use fatty acids as energy substrates (Panov et al, 2014;Schönfeld and Reiser, 2013). However, although this is true for neurons, the carnitine palmitoyl transferase (CPT) system, which allows the entry of long-chain fatty acids into the mitochondria for ß-oxidation, is functional in astrocytes (Jernberg et al, 2017;Panov et al, 2014) and in embryonic (Xie et al, 2016) and adult (Knobloch et al, 2017) neural stem cells. The role of carnitine in its anti-inflammatory or energetic functions remains to be elucidated in this model and may constitute for the future a starting point for the development of innovative therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, in HSCs, a decrease in FAO leads to an increase of symmetric divisions giving rise to differentiating cells, which ultimately leads to exhaustion of the stem cell pool (Ito et al, 2012). Remarkably, deficiencies in FAO also increase the rate of mouse NSC symmetric differentiating divisions, at the expense of asymmetric divisions that normally maintain the pool of stem cells (Xie et al, 2016).…”
Section: Lipids and Asymmetric Cell Divisionmentioning
confidence: 91%
“…Strikingly, the presence of malonyl-CoA, which inhibits the rate-limiting step in FAO, was sufficient to induce exit from quiescence to proliferation (Knobloch et al, 2017), indicating that the tight regulation of FAO plays an important role in the regulation of NSPC behavior. FAO is also required in embryonic NSCs, where CPT1A and the breakdown of FAs from LDs have been shown to regulate the asymmetric divisions and maintenance of these stem cells (Xie et al, 2016).…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%